2015
DOI: 10.1007/s11934-015-0495-9
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescence Imaging with Intraoperative Administration of Indocyanine Green for Robotic Partial Nephrectomy

Abstract: Near-infrared fluorescence (NIRF) imaging with intraoperative administration of indocyanine green (ICG) is a technology with emerging applications in urologic surgery. ICG is a water-soluble dye that fluoresces bright green when viewed under near-infrared light (700-1000 nm). This technology has been applied to robotic partial nephrectomy, first to potentially allow for the differentiation of renal tumor from normal parenchyma. In this application, it has been hypothesized that normal kidney tissue fluoresces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…However, a separate study from the same group found that NIR with indocyanine green was unreliable in identifying malignancy, as correlated with final histology [46].…”
Section: Near Infrared Imaging With Fluorophoresmentioning
confidence: 99%
“…However, a separate study from the same group found that NIR with indocyanine green was unreliable in identifying malignancy, as correlated with final histology [46].…”
Section: Near Infrared Imaging With Fluorophoresmentioning
confidence: 99%
“…There have been many techniques described to induce renal cooling including peri-renal ice slush, cold saline surface irrigation, endoscopic retrograde renal cooling, and trans-arterial renal hypothermia, with varying degrees of success. Kaouk et al, described intracorporeal cooling which placement of the kidney inside an Endocatch II bag filled with ice slush to achieve a temperature of [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] degrees [23]. A recent method that avoids the use of a cumbersome bag, and is not limited to the retroperitoneal approach was by placing ice on the psoas muscle and then over the renal parenchyma, with a laparoscopic sponge placed on the small bowel to prevent bowel cooling ( [23].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Recently, the use of a near-infrared fluorescence (NIRF) imaging system using indocyanine green (ICG) dye has been described during robotic partial nephrectomy as an adjunctive means of identifying renal vasculature and tumour clearance. ICG is a water-soluble dye that fluoresces bright green when viewed under near-infrared light (700-1000 nm) [4]. This technology has been applied to robotic partial nephrectomy, to look for the differentiation of renal tumor from normal parenchyma [4].…”
Section: Mini Reviewmentioning
confidence: 99%
“…ICG is a water-soluble dye that fluoresces bright green when viewed under near-infrared light (700-1000 nm) [4]. This technology has been applied to robotic partial nephrectomy, to look for the differentiation of renal tumor from normal parenchyma [4]. In this application, it has been hypothesized that normal kidney tissue fluoresces green, while the tumor commonly remains hypofluorescent, thereby aiding tumor excision [4].…”
Section: Mini Reviewmentioning
confidence: 99%
See 1 more Smart Citation